SEJARAH PERKEMBANGAN SISTEM PENDIDIKAN MADRASAH SEBAGAI LEMBAGA PENDIDIKAN ISLAM - Yayah Chairiyah (MA'ALIM: Jurnal Pendidikan Islam, 2021)
Education has a very important role to prepare the nation's and religion’s generation. Quality of education today is a very important for human life. The progress of a nation or state is depende on the education of a nation. Madrasah as educational institutions in Indonesia are educational institutions under the auspices of the Indonesian Ministry of Religion. Currently, madrasah are able to show that they are modern Islamic educational institutions that can be seen from their physical and academic appearance, madrasah already have complete infrastructure facilities to support scientific development (learning process), qualified educators according to their knowledge, good educational staff and other supporters. Madrasah also have the vision, mission and goals of the institution that must be considered in curriculum development. Each educational institution has varied differences, which show the strengths and opportunities of each educational institution. The facilities and facilities owned by the madrasah are the teacher's consideration in developing the curriculum. This requires madrasah as schools with Islamic characteristics in developing their curriculum to have scientific programs related to religion and science technology as well as soft skills, independence and leadership.Key words: educational history, education system, Islamic educational institutions, madrasah.